PENGARUH TINGKAT PERPUTARAN PERSEDIAAN TERHADAP MODAL KERJA BERSIH STUDI PADA KOPERASI PETERNAK GARUT SELATAN (KPGS) CIKAJANG - Urip Sudiana; Lukmanul Hakim (Sekolah Tinggi Ilmu Ekonomi DR KH EZ Mutaqien, 2022)
This research is motivated by an indication that the net working capital of the Cikajang South Garut Breeders Cooperative (KPGS) has fluctuated. and has tended to decrease over the last 5 years. The purpose of this study was to determine the effect of inventory turnover on net working capital at the South Garut Farmers Cooperative (KPGS) Cikajang. The research method used is descriptive method with a quantitative method approach. Based on the analysis of the data obtained, the development of inventory turnover tends to increase and net working capital tends to decrease. While the influence of the level of inventory turnover on net working capital seen from the value of the Pearson product moment correlation coefficient is 0.882, it can be interpreted that the relationship between the level of inventory turnover and net working capital has a very strong relationship and a negative relationship. The coefficient of determination is 77.7%, and the remaining 22.3% is influenced by other factors not examined. Regression test with Y = 6,264,751,301.00 – 1,667,743.489 X, which means that for each addition of one unit of Inventory Turnover then the value of Net Working Capital will decrease or decrease by 1,667,743.489.